Workplace reform with changing management through the user participation workshop: the case study of Seiyo City office / Ikumi Egawa ... [et al.] - Egawa, Ikumi; Kawakita, Kentaro; Katagiri, Yuki; Masuda, Ami; Ishiyama, Nozomi; Yuji, Matsumoto; Li, Andrew I-kang; Naka, Ryusuke (2018)
In this paper, we describe about workplace reform aimed at improving productivity of General Affairs and Policy Planning department of Seiyo office, by changing management through the user participation workshop at 4th floor of Seiyo city office, and about the changes of workplace reform. The purpose of this research is to find the changes that are worker's behaviour and worker’s awareness of workplace by workplace reform. We surveyed changes, worker's behaviour and worker's awareness of workplace, by workplace reform at 4th floor of Seiyo office as one case. At workplace reform, in order to create a place where new work style can be practiced, we conducted the user’s participation workshops with workers 6 times. Through the conducted workshops, concept of work style and plan of renovation were proposed. In addition, we surveyed two methods of questionnaire survey and observation survey three times: before the workplace renovation, 3 months after the renovation, and 1 year and 3 months after the renovation. In the questionnaire survey of 3 months after the renovation, it shows that the opinions of the workers were divided between pros and cons against workplace reform. However, the survey of 1 year and 3 months after the renovation shows that almost all workers were satisfied with the new environment. In addition, we found that a positive correlation between participation rate of workshops and in satisfaction increased. The findings suggest the importance of workshops for workplace reform. In the Observation Survey, it shows that the workers selected a place freely where they can work comfortably after workplace reform. For example, they work in refresh space. In addition, the survey suggests that the floor became lively from the rise of the conversation participation rate. Also, as features of work style, after workplace renovation, it suggests that they become conscious of the work style they clearly differentiate between short intermittent works separated by conversation and phone and personal work on concentration.